2019
DOI: 10.2147/ott.s214611
|View full text |Cite
|
Sign up to set email alerts
|

<p>Epidermal growth factor receptor (<em>EGFR</em>) gene alteration and protein overexpression in Malaysian triple-negative breast cancer (TNBC) cohort</p>

Abstract: BackgroundEpidermal growth factor receptor (EGFR) is a member of the ErbB family of tyrosine kinase receptor proteins that plays important roles in tumour cell survival and proliferation. EGFR has been reported to be overexpressed in up to 78% of triple-negative breast cancer (TNBC) cases suggesting it as a potential therapeutic target. The clinical trials of anti-EGFR agents in breast cancer showed low response rates. However, a subgroup of patients demonstrated response to EGFR inhibitors highlighting the ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 40 publications
1
26
0
Order By: Relevance
“…In the present study, the mean age of TNBC patients at diagnosis ± (SD) was 48.9 ± 9.67 years. A recent study on Malaysian TNBC patients reported the range of age at diagnosis of Malaysian TNBC patients as from 26-89-years (Zakaria et al, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…In the present study, the mean age of TNBC patients at diagnosis ± (SD) was 48.9 ± 9.67 years. A recent study on Malaysian TNBC patients reported the range of age at diagnosis of Malaysian TNBC patients as from 26-89-years (Zakaria et al, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…The EGFR, which stimulates the cancer proliferation via PI3K/RAS signaling, the repair of DNA damage and metastasis [19][20][21][22][23], is overexpressed in various tumors, e.g., TNBC (52-54%) [24,25], lung cancer (40%) [26,27], glioblastoma (50%), head and neck cancer (80-90%) [24,25,28], ovarian, cervical, bladder, gastric, endometrial and colorectal cancers [29]. EGFR is more predominant in TNBCs than other breast cancers [24,30], and usually correlates with tumor invasion and poor prognosis.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly the expression of ER and PR or all negative expression of breast cancer cells determines the treatment choices or deferment of few treatment protocols. This aspect of molecular subtype of breast cancer have been studied by the researchers but in isolation [14,15,16]. Recent years the pathologic staging of breast cancer has been upgraded by addition of molecular subtype.…”
Section: Fig 1 the Egfr Signaling Pathway And Therapeutic Interceptionsmentioning
confidence: 99%